‘Per desiderio di farsi onore’: Singers and the Adaptation of Arias in Italian drammi per musica of the Early Eighteenth-Century Italy - Desler Anne (Musicology Today)
Within the aesthetic framework of the work concept and author-centred approach to music history, the practice of aria substitution in the eighteenth-century Italian dramma per musica has frequently been viewed as hostile interference with the composer’s authorial intention and attributed to singers’ vanity, laziness and ignorance. However, the substitution of both the texts and musical settings of arias constituted the default production practice in a period in which scores were not conceptualised as fixed texts but functioned as performance materials for specific productions. Moreover, the practice of aria substitution was deeply rooted in the socio-cultural context of opera production and the arts consumption practices of the social elite. A manifestation of period preoccupation with displaying and gauging rank and status, it was crucial to singers’ professional success.